FRI0390 Use of Muscle Biopsies for The Diagnosis of Systemic Vasculitis in A Rheumatology Service. (15th July 2016) - Rodríguez-Muguruza, S.; Sanint, J.; Saenz-Sarda, X.; Prior-Español, A.; García-Mira, Y.; Holgado, S.; Mateo, L.; Cañellas, J.; Martinez-Morillo, M.; Tena, X.; Casas, I.; Mate, J.L.; et al.
Abstract : Background: Systemic vasculitis (SV) comprises a group of diseases characterized by inflammation of vessels in various organs. Histopathological confirmation is required for the diagnosis. The biopsy of an involved organ is invasive and carries the risk of complications. By contrast, gastrocnemius muscle biopsy is simple and minimally invasive technique that may be performed by a rheumatologist. Objectives: To evaluate the diagnostic use of muscle biopsies for the diagnosis of SV. Methods: Retrospective study 1984 - 2015. Center: tertiary academic hospital, referral area 850.000 inhabitants. We analyzed the database of all muscular biopsies performed at our hospital. We selected patients undergoing a muscular biopsy for possible diagnosis of SV and we analyzed the clinical, laboratory, neurophysiological and pathologic data. Biopsies were classified as positive (presence of necrotizing vasculitis or non necrotizing vasculitis seen by optical microscopy) or negative for vasculitis. Muscular biopsy was performed in all cases at the medial gastrocnemius muscle ("open" and unilateral) by a rheumatologist. The diagnosis of SV was based on clinical, serological and histological data. Results: A total of 619 muscular biopsies were performed, 55 were indicated with suspicion of SV, 52.7% female, 47.3% male, median age 64.4 years (DS 15.22); 47 (85.4%) were positive (sensitivity of 85%) and 8 (14.6%) were negative. The positive biopsy group showed more electromiographic alterations (p=0.01) than negative group. Furthermore, the positive biopsy group showed more frequently systemic manifestations such as: weight loss, myalgia, paresthesias, purpura and testicular pain but these differences were not statistically significant. No complications were encountered in the procedure. Conclusions: Our results suggest that muscle biopsy is a simple, clinically useful, safe and minimally invasive procedure for the diagnosis of SV with high sensitivity. No significant differences were observed in clinical or analytical features between patients with positive or negative biopsy, except in electromyography patients with positive biopsy had more a frequent pathological pattern. Disclosure of Interest: None declared